2016
DOI: 10.1007/s10796-016-9675-5
|View full text |Cite
|
Sign up to set email alerts
|

Driving innovation through big open linked data (BOLD): Exploring antecedents using interpretive structural modelling

Abstract: Innovation is vital to find new solutions to problems, increase quality, and improve profitability. Big open linked data (BOLD) is a fledgling and rapidly evolving field that creates new opportunities for innovation. However, none of the existing literature has yet considered the interrelationships between antecedents of innovation through BOLD. This research contributes to knowledge building through utilising interpretive structural modelling to organise nineteen factors linked to innovation using BOLD identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 31 publications
0
65
0
1
Order By: Relevance
“…For example, analysing if attitude or behavioural intention is a better measure of technology acceptance, Pynoo et al (2007) showed FC to be a significant predictor of AT in a mandatory setting. Facilitating conditions describes the perceived importance of organizational and technical infrastructure to support systems use (Venkatesh et al 2003;Dwivedi et al 2016). The direct path from FC to AT can also imply that the technical and organizational infrastructure relating to an IS/IT such as help desks and training programs may shape the user's attitude tow.ard the IS/IT.…”
Section: Masem Model For Proposed Theoretical Modelmentioning
confidence: 99%
“…For example, analysing if attitude or behavioural intention is a better measure of technology acceptance, Pynoo et al (2007) showed FC to be a significant predictor of AT in a mandatory setting. Facilitating conditions describes the perceived importance of organizational and technical infrastructure to support systems use (Venkatesh et al 2003;Dwivedi et al 2016). The direct path from FC to AT can also imply that the technical and organizational infrastructure relating to an IS/IT such as help desks and training programs may shape the user's attitude tow.ard the IS/IT.…”
Section: Masem Model For Proposed Theoretical Modelmentioning
confidence: 99%
“…In innovation, bureaucratic and political factors are found to be more dominant than technological, economic and politico-economic perspectives (Gonzalez-Zapata and Heeks 2015). The links between transparency, openness, accountability, participation, and trust and data-driven innovation are often vague and unclear, as shown in the paper of Dwivedi et al (2017) of this special issue. This is due to the high dependency between the concepts, but also due to the different conceptualizations.…”
Section: Factors Influencing Data-driven Innovationmentioning
confidence: 99%
“…This could provide a useful prescription for policymakers to implement in addition to consideration of this research. Moreover, the researchers could also consider implementing ISM methodology (Al-Muftah et al 2018;Dwivedi et al 2017a;Hughes et al 2016;Janssen et al 2018) to understand the driving and dependent barriers. The citizens are one of the most important stakeholders of such developments.…”
Section: Limitations and Future Scopementioning
confidence: 99%